Zinc, Copper, C-Reactive Protein And Lipid Peroxidation In Chronic Liver Diseases - SUNEEL.B,; BALAKRISHNA.D,; SRIDHAR.M,; APARNA.R.R.,; DR.SOWJANYA.B, (International Journal of Pharma and Bio Sciences, 2012)
Lipid peroxidation is an auto catalytic mechanism leading to oxidative destruction of liver. Alters the Zn+, Cu++,CRP levels in chronic liver disease. In liver disorders decreased Zn+ levels due to poor appetite during the infection with the help of leukocyte endogen mediator and uptake of more Zn to synthesize nucleic acid, protein and enzymes by liver cells, Cu++ levels are high in liver disease because of decreased synthesis of cereloplasmin by the liver. CRP is a inflammatory marker it is elevated in liver disease. The study was carried out in 45 subjects with liver disease, Zn+ was significantly (p 0.001) decreased. CRP(0.001), Cu(p 0.001) and MDA(0.001) significantly elevated compared with those of healthy individuals. Thus the study supports the association of trace elements such as Zn+, Cu++, CRP and lipid peroxidation in liver diseases.